Anomalous Origin of Left Coronary Artery from the Pulmonary Artery (ALCAPA) in an Infant - A Case Report - Jabbar, Abdul; Hussain, Manzoor; Rima, Rezoana; Mamun, Mohammad Abdullah Al; Echo, Nowshika Sharmeen (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2016; VOL 40 (1) :39-43